Fast burn! : the power of negative energy balance - Smith, Ian, 1969- (St. Martin's Press, 2021)
"A motivational diet plan to blast fat-and keep it off-by Ian K. Smith, M.D., the #1 New York Times bestselling author of Clean & Lean. New York Times bestselling author-and new anchor host of the syndicated television show The Doctors-Ian K. Smith, M.D.'s unique new plan takes intermittent fasting to the next level, combining the power of time-restricted eating with a detailed program that flips the body into a negative energy state, scorching fat on the way to weight loss and physical transformation. Many IF books leave readers to figure out what and how much they should eat during their feeding window, and even how long to fast each day. Smith knows that even readers highly motivated to change their weight and their health need marching orders, and they're all here in Fast Burn!'s nine-week program. Dr. Ian believes in cleaner eating-forget perfect-and the two positively disruptive Jigsaw Weeks he works into his Fast Burn! program not only mix things up so Fast Burners stay on track, but introduce refreshing and less structured plant-based weeks to the program. Fast Burn! goes beyond the daily meal plan, but also includes simple and achievable exercises-with both gym and out-of-gym options-for every week as well as thirty-three recipes focusing on improved calorie quality, including the plan's signature Burner Smoothie, to use throughout the three stages of the program"--